Evaluasi Kebijakan Pembangunan Pamsimas di Desa Lubuk Ulak Kecamatan Muara Pinang Kabupaten Empat Lawang - Wance Supriadi; Ika Devy Pramudiana; Sapto Pramono (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community-Based Drinking Water and Sanitation Provision Program (PAMSIMAS) aims to increase access to clean water and proper sanitation in rural areas. However, the implementation of this program in several villages, including in Lubuk Ulak Village, Muara Pinang District, Empat Lawang Regency, still faces various challenges. This research aims to evaluate the PAMSIMAS development policy in the village, focusing on the effectiveness of implementation, the challenges faced, and its impact on the local community. This study uses a descriptive qualitative approach with a case study design. The data collection techniques used were in-depth interviews, observations, and document studies related to the implementation of PAMSIMAS. The collected data was analyzed thematically to find patterns relevant to the research objectives. The results show that although PAMSIMAS has succeeded in providing clean water infrastructure, there are still problems in terms of water resource management, community participation, and facility sustainability. Lack of technical training for local managers and weak coordination between stakeholders led to the insustainability of programs at the village level. In conclusion, PAMSIMAS in Lubuk Ulak Village needs improvements in planning, community involvement, and institutional capacity strengthening. Further research is needed to explore the sustainability of the program and the active role of communities and governments in sustainable clean water management.